CEO characteristics and disability employment of listed firms. Evidence from India - Kofi Mintah Oware; Gilbert K. Amoako (Cogent Business & Management, 2022)
Using the stewardship theory and theory of fear of failure as the underlying theory, the study focuses on investigating CEO characteristics and disability employment of listed firms in India. The study employed descriptive statistics and feasible generalised least square (FGLS) assumption to analyze data from 80 Indian listed firms with 800 firm-year observations from 2010 to 2019. We find that CEO age and CEO tenure have a strong and positive correlation. The first findings show that ageing CEOs are insignificant to exhibit any levels of disability employment in India. This study suggests that ageing CEOs do not see disability employment as a welfare cost or employment that can lead to a consequential profit. The second findings show that firms with long-tenured CEOs exhibit a higher level of disability employment. This outcome does not conflict with the assumption that the CEO has a sense of responsibility to achieve what is right and protect the firm's assets. Lastly, the study shows that female CEOs exhibit higher levels of disability employment in India. The study is limited to firms with data on people with disabilities. Using the Indian stock market as the only study source may affect the study's generalisation. Also, small firms that employ disabled persons are not on the stock market and may potentially undermine the study's scope. Examining CEO characteristics (CEO age, CEO tenure and CEO gender) on disability employment deepens disability studies in emerging markets.
Keywords: 650; India; CEO characteristics; Disability employment; Paper type -Research paper; Stewardship theory; Theory of fear of failure